2004
DOI: 10.1055/s-2004-828703
|View full text |Cite
|
Sign up to set email alerts
|

Distal Anterior Inferior Cerebellar Artery Aneurysm Masquerading as a Cerebellopontine Angle Tumor: Case Report and Review of Literature

Abstract: We present the case of a distal anterior inferior cerebellar artery (AICA) aneurysm masquerading as a cerebellopontine angle tumor in a 60-year-old righthanded man with previously undiagnosed polyarteritis nodosa (PAN). The patient presented with a 2-month history of progressive right-sided hearing loss, intermittent severe headache, and sudden onset of complete facial paralysis 3 weeks before admission. Magnetic resonance imaging, including postgadolinium images, showed a 1.2-cm heterogenously enhancing mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…24,31,40,51 In a series of more than 3500 saccular aneurysms treated surgically during a 16-year period, Gonzalez and colleagues 19 reported that a mere 34 (1.7%) aneurysms arose from the AICA. Of these, 21 became symptomatic with subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…24,31,40,51 In a series of more than 3500 saccular aneurysms treated surgically during a 16-year period, Gonzalez and colleagues 19 reported that a mere 34 (1.7%) aneurysms arose from the AICA. Of these, 21 became symptomatic with subarachnoid hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…A few cases of thrombosed large AICA aneurysm have been reported, 1,6,7,11,13,16) including local association with acute hematoma. 6,16) One patient complained of sudden onset of occipital headache, nausea, and vomiting, 6) and the other patient suddenly developed facial numbness and headache.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][8][9][10][11][12]14,15,17) Progressive growth of an aneurysm of the AICA generally manifests as various cerebellopontine angle syndromes such as oculomotor nerve palsy, trigeminal sensory loss or neuralgia, sixth cranial nerve palsy, seventh cranial nerve palsy, vertigo, tinnitus, hearing loss, lower cranial nerve palsy, and ataxia. 1,6,7,10,11,13,14,16) Rapid deterioration of neurological symptoms generally indicates rupture of an aneurysm. Subarachnoid hemorrhage may subsequently cause dyspnea, arrhythmia, and death after these cerebellopontine angle syndromes occur.…”
Section: Introductionmentioning
confidence: 99%
“…MR angiography has detected increasing numbers of cerebral aneurysms in patients with collagen diseases, with a total of 48 cases reported up to September 2008, including 25 patients with systemic lupus erythematosus, 1,10,11,14,18-20,22,25,27,30-33,37,42, 43,52) 16 patients with polyarteritis nodosa, 2,8,9,24,28,29,35,36,41,44,45,[49][50][51] 5 patients with scleroderma, 3,17) and 2 patients with CREST syndrome. 38,56) To determine the specific features of cerebral aneurysm in patients with collagen diseases, we reviewed the 48 reported cases and identified the following four characteristics.…”
Section: Discussionmentioning
confidence: 99%